Lentiviral Mediated ADA2 Gene Transfer Corrects the Defects Associated With Deficiency of Adenosine Deaminase Type 2 - Hong, Ying; Casimir, Marina; Houghton, Benjamin C.; Zhang, Fang; Jensen, Barbara; Omoyinmi, Ebun; Torrance, Robert; Papadopoulou, Charalampia; Cummins, Michelle; Roderick, Marion; Thrasher, Adrian J.; Brogan, Paul A.; et al. (Frontiers in Immunology, 2022)
Deficiency of adenosine deaminase type 2 (DADA2) is an autosomal recessive disease caused by bi-allelic loss-of-function mutations in ADA2. Treatment with anti-TNF is effective for the autoinflammatory and vasculitic components of the disease but does not correct marrow failure or immunodeficiency; and anti-drug antibodies cause loss of efficacy over time. Allogeneic haematopoietic stem cell transplantation may be curative, but graft versus host disease remains a significant concern. Autologous gene therapy would therefore be an attractive longer-term therapeutic option. We investigated whether lentiviral vector (LV)–mediated ADA2 gene correction could rescue the immunophenotype of DADA2 in primary immune cells derived from patients and in cell line models. Lentiviral transduction led to: i) restoration of ADA2 protein expression and enzymatic activity; (ii) amelioration of M1 macrophage cytokine production, IFN-γ and phosphorylated STAT1 expression in patient-derived macrophages; and (iii) amelioration of macrophage-mediated endothelial activation that drives the vasculitis of DADA2. We also successfully transduced human CD34+ haematopoietic stem progenitor cells (HSPC) derived from a DADA2 patient with pure red cell aplasia and observed restoration of ADA2 expression and enzymatic activity in CD34+HSPC, alongside recovery of stem-cell proliferative and colony forming unit capacity. These preclinical data now expand the evidence for the efficacy of gene transfer strategies in DADA2, and strongly support clinical translation of a lentivirus-mediated gene therapy approach to treat DADA2.